Polystichum kuankuoshuiense (sect. Sphaenopolystichum, Dryopteridaceae), a new fern from Guizhou, China - Wang, Bo; Sun, Qing-Wen; Wang, Ze-Huan; Zhang, Li-Bing (Phytotaxa, 2023)
Polystichum kuankuoshuiense (Dryopteridaceae), a new species from Kuankuoshui Nature Reserve, Suiyang County, Guizhou, China, is described and illustrated. It is a member of P. sect. Sphaenopolystichum and similar to P. auriculum, P. bifidum, and P. suiyangense but differs from them in its rhizome, scale color, and pinna morphology. Quite surprisingly, the new species is not closely related to these morphologically similar species. The new species is currently known only from the type locality and is classified as CR (critically endangered) following the IUCN criteria.